A facile microwave synthesis of PbS:Sr nanoparticles and their key structural, morphological, optical, photoluminescence, dielectric and electrical studies for optoelectronics. (10th January 2020) - Shkir, Mohd; Khan, Aslam; Hamdy, M S; AlFaify, S
Abstract: Herein, various Strontium (Sr) concentrations doped Lead Sulfide (PbS) (PbS:Sr) nanoparticles (NPs) were synthesized and subjected to key parameters analysis. EDX/SEM mapping analysis confirms the presence of Sr and its harmonized allocation in the final product. Spherical NPs morphology was approved by field emission scanning electron microscopy (FE-SEM) analysis with tiny dimension grains formation. The grain size was observed to be approximately 55 nm; crystallite sizes calculated was found to be in the range of 18–21 nm. Slight shift in vibrational modes was noticed owing to low dimension NPs and approved a single phase. Diffused reflectance spectra were recorded, and direct energy gap was found in the range of 0.70–0.78 eV, which was much larger compared to the bulk (0.41 eV) one. PL emission spectra contained three emission peaks at 519 nm (major), 556 nm and 702 nm (broad) when excited at 450 nm. Also, the quenching in PL intensity was observed with Sr doping. The value of dielectric constant was noticed in the range of 25 to 57. The enhancement in total electrical conductivity was observed from −11.67 to −7.83 S cm −1 at 10 kHz; and from −4.30 to 3.42 S cm −1 at 10 MHz. The enrichment of physical properties of Sr doped PbS signify its suitability in optoelectronics.